Laccase Activity in Fungus Cryphonectria parasitica Is Affected by Growth Conditions and Fungal–Viral Genotypic Interactions - Lucija Nuskern; Mirta Tkalec; Bruno Srezović; Marin Ježić; Martina Gačar; Mirna Ćurković-Perica (Journal of Fungi, 2021)
Laccase activity reduction in the chestnut blight fungus Cryphonectria parasitica usually accompanies the hypovirulence caused by the infection of fungus with Cryphonectria hypovirus 1 (CHV1). However, the different methods utilized for assessing this phenomenon has produced varied and often conflicting results. Furthermore, the majority of experimental setups included only one prototypic system, further confounding the results. Considering the diversity of fungal isolates, viral strains, and variability of their effects on the phytopathogenic process observed in nature, our goal was to ascertain if laccase activity variability is affected by (1) different C. parasitica isolates infected with several CHV1 strains, and (2) growth conditions. We have demonstrated that some CHV1 strains, contrary to previous assumptions, increase the activity of C. parasitica laccases. The specific fungal isolates used in the experiments and culture conditions also affected the results. Furthermore, we showed that two commonly used laccase substrates, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) and 2,4-dimethoxyphenol, cannot be used interchangeably in C. parasitica laccase activity measurements. Our results illustrate the importance of conducting this type of study in experimental systems and culture conditions that resemble natural conditions as much as possible to be able to infer the most relevant conclusions applicable to natural populations.